THE ORAL HISTORY OF FORGOTTEN WARS: THE MEMOIRS OF VETERANS OF THE WAR IN ANGOLA/GENNADY SHUBIN - Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2011)
With the commemoration of the battles around Cuito Canavale coming up, various authors are striding Angolan battlefields again. In South Africa a variety of publications is seeing the light. Unfortunately many of these are by former senior officers highlighting their own interpretation of the war, as did many previous publications in South Africa. Many publications here are espousing one side of the war. The role of Special Forces is but one example. This trend was set in the 1980s and seems to continue in South Africa. The role of Special Forces - as if others were not involved - deserves a lot of attention. More so the role of other actors such as the Angolan armed forces (FAPLA), the Cubans and the Soviets is mostly ignored except for some stereotyping underpinned by an ideology from times gone by - indeed a sad state of affairs.